Citrate-induced local ionized calcium decrease in pediatric hemodialysis settings: An in-vitro study. Issue 4 (July 2022) - Novljan, Gregor; Kolar, Mitja; Kastelec, Lea; Battelino, Nina
Background: Citrate is instilled into the dialysis catheter to prevent clotting and to maintain patency between dialysis sessions. A significant amount of citrate leaks from the catheter at the injection time, which decreases the blood ionized calcium concentration (Ca 2+ ) due to chelation. We aimed to evaluate the local impact of concentrated (i.e. 30%) citrate spilling on Ca 2+ at the catheter tip in real-time pediatric conditions. Methods: An in-vitro model was constructed, involving an ion-selective electrode (Ca-ISE). A pre-curved catheter and the Ca-ISE were submerged in a glass vessel with the tips positioned adjacent to each other. The vessel was filled with 30 and 80 ml of normal saline with added calcium to simulate normal right atrium size in children and adults, respectively, and normal blood Ca 2+ . The amount of instilled citrate matched the filling volume of the catheter. Measurements were performed with 4% and 30% citrate solutions. Results: The mean Ca 2+ measured at the tip of the catheter was 0.457 and 0.058 mmol/l when using 4% and 30% citrate, respectively ( p  < 0.001). The mean Ca 2+ recorded in 30 and 80 ml after instilling 30 % citrate was 0.058 and 0.055 mmol/l, respectively ( p  = 0.878). Conclusions: The spilling of 30% citrate caused a strikingly greater decrease of Ca 2+ at the catheter tip than the standard 4% citrate. The atrial volume did not influence the test results implying similar safety concerns for pediatric and adult patients. The used static experimental setting might have overestimated the spilling effect.